Antecedents of Consumer Purchase Intention Towards Organic Food - Marshella Shafira Putri Siwalette; Wafa Azzahra Hassya Harahap; Sabina Keyla Aisha; Fatik Rahayu (Golden Ratio of Data in Summary, 2024)
This study analyzes the factors that influence consumer intention to buy organic food in Indonesia. Against the backdrop of increasing health and nutrition awareness, this study examines the role of functional value, consumer innovation, eco-friendly beliefs, health benefits, and knowledge of organic food. Data was collected through a consumer survey which showed that demand for organic food grew by 21% in 2018. Descriptive statistics and hypothesis testing were used as data analysis methods. The results showed that all variables studied had a significant positive effect on consumer purchase intention. The main purchase intention is the functional value and quality of organic products, as well as consumer knowledge of health benefits and trust in environmentally friendly products. This study provides practical insights for organic food industry players to develop relevant and effective marketing strategies to increase consumer interest. In addition, the findings make an academic contribution to the understanding of the factors that influence consumer purchasing behavior towards organic products. This study also identifies existing limitations and offers recommendations for further research to deepen the understanding of consumer behavior towards organic food.